A novel terpolymer nanocomposite (carboxymethyl β-cyclodextrin–nano chitosan–glutaraldehyde) for the potential removal of a textile dye acid red 37 from water - Elbadawy, Hemmat A.; El-Dissouky, Ali; Hussein, Seham M.; El-Kewaey, Sara R.; Elfeky, Souad A.; El-Ghannam, Gamal (Frontiers in Chemistry, 2023)
Carboxymethyl β-cyclodextrin–nanochitosan–glutaraldehyde (CM-βCD:nChi:Glu) terpolymer was prepared as a nano-adsorbent for the removal of the anionic textile dye, acid red 37. The terpolymer nanocomposite formation and characterization were clarified by FTIR, XRD, scanning electron microscopy, TEM, Brunauer–Emmett–Teller specific surface area (BET-SSA), and zeta potential. The removal of the textile dye was investigated by using the batch adsorption method, investigating the effect of pH, dye concentration, adsorbent dose, contact time, and temperature. The results revealed that the maximum removal efficiency of 102.2 mg/L of the dye is about 99.67% under pH 6.0, the optimal contact time is 5 min, and the adsorbent dosage is 0.5 g/L. At 29°C; the adsorption capacity increased from 81.29 to 332.60 mg/g when the initial concentration of the dye was increased from 40.97 to 212.20 mg/L. Adsorption kinetics fitted well with the pseudo–second-order model with a good correlation (R2 = 0.9998). The Langmuir isotherm model can best describe the adsorption isotherm model. Based on the experimental results, the CM-βCD:nChi:Glu terpolymer has a promising potential as an efficient novel adsorbent for the removal of textile dye acid red 37 from contaminated water. This study’s preparation techniques and demonstrated mechanisms offer valuable insights into the adsorbent–adsorbate interactions mechanism, analysis, challenges, and future directions of beta-cyclodextrin/chitosan–based adsorbents in wastewater treatment.